Cd-Rom and Access to Information - Chacón Alvarado, Lucía (1990)
The scientific and technological advances in the world and his application in the different areas of the knowledge have developed a new electronic age. Example of the previous thing they are the CD-ROM that it has been penetrating into the libraries of a very effective way and of a form very sophisticated it allows the access to the information.